Vesicular movements in the growth cone. (October 2018) - Nozumi, Motohiro; Igarashi, Michihiro
Abstract: Growth cones, which are the highly motile tips of extending neuronal processes in developing neurons, have many vesicles. These vesicles are likely essential for the membrane expansion that is required for nerve growth, and probably coordinate with rearrangement of the cytoskeletons. Such mechanisms are poorly understood from molecular and cell biological aspects. Recently, we used superresolution microscopic approaches and described new mechanisms that are involved in the interaction between the vesicles and F-actin in the leading edge of the peripheral domain. Vesicles mainly accumulate in the central domain of growth cones. However, the dynamics of vesicles in each domain, for example, clathrin dependency, are totally distinct from each other. Here, we discuss the diversity of the dynamics of vesicular and related proteins that play different roles in nerve growth. Highlights: We provide an overview of the vesicles enriched in growth cones. These vesicles are involved in axon growth and interact with the cytoskeleton. Vesicles in the P-domain, but not the C-domain, are linked to F-actin. Superresolution microscopy reveals a new mechanism for vesicles in the leading edge.